A TEXTBOOK OF TEORI PUISI USING CONTEXTUAL APPROACH IN THE PROCESS OF TEACHING LEARNING LITERATURE - Ayu Istiana Sari, Ch. Evy Tri Widyahening & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2017)
The aims of this study are 1) to describe and explain the quality of a textbook of teori puisiwhich was used by students in English Department, Teacher Training and EducationFaculty, in Surakarta; 2) to determine whether the textbook which was arranged by usingcontextual approach is more effective than other textbooks of teori puisi. The researchmethod used the design of Research and Development. The procedure of Research andDevelopment was 1) effectiveness test of a textbook of teori puisi; and 2) dissemination:printing and publishing of a textbook of teori puisi with the number of ISBN. Thepopulation of this research was all students of English Department in the third semester inSurakarta. Technique of collecting data was done through observation, informantinterviews, document analysis, the result of studentsâ evaluation about teori puisi, andquesionairre for the lecturers. Validity and reliability tests used Correlation of Productmoment. Technique of data analysis used t-test independent. The result of this study showedthat a textbook of teori puisi using contextual approach was effective in teaching learningliterature.Key words: A textbook of Teori Puisi, Research and Development, Contextual Approach